Postsouthern cartographies: capital, land and place from 'The Moviegoer' to 'A man in full' - Bone, Martyn (2002)
This thesis takes a historical-geographical materialist approach to the capitalist production and literary representation of "place" in the American South between the 1960s and 1990s. Part 1 provides literary-historical and theoretical context. Chapter 1 considers how the Agrarians and their literary critical acolytes defined the "sense of place" of "Southern literature." However, the chapter also recovers an aspect of Agrarianism suppressed by later Southern literary critics: the critique of modern (finance) capitalist abstraction expressed through the Agrarians' "proprietary ideal." Drawing also on postmodern theory, Chapter 2 theorises a postsouthern literary theory of place.